(untitled) (Journal of NELTA, 2015)
Smart teacher smart class (STSC) is a portal developed by Dnet which contains curriculum, teachers’ guide, education policy, textbook, lesson plan, multimedia contents, and teaching-learning strategies on different subjects aiming to provide content and pedagogical support to the secondary school teachers in Bangladesh. Making an offline CD, the STSC portal is provided to the respective teachers of secondary schools Dnet works with. The regular use of the STSC portal helps the teachers to improve their knowledge about effective teaching-learning techniques. The study was designed as one group pre-test post-test quasi-experimental method to find the effect of STSC portal on secondary school English teachers’ English language teaching knowledge (ELTK). Twenty eight English teachers from 14 secondary schools were selected purposively to form the group and the tests were administered on them considering 6 months intervention (STSC portal) period. The test was adapted from Cambridge language teaching knowledge (TKT) test focusing on different ELT aspects. The tests scores of the teachers were categorized in 4 knowledge levels: limited, basic, deep and extensive. The findings of the study show that the STSC portal induces a significant improvement of the teachers’ ELTK. Most of the teachers showed better performances in the post-test than the pre-test. Moreover, significance (0.001) and effect size score (0.91) also depict a clear and large effect in enhancing teachers’ ELTK. DOI: http://dx.doi.org/10.3126/nelta.v19i1-2.12087 Journal of NELTA, Vol 19 No. 1-2, December 2014: 147-157